Injection moulding parameters and performance of rice husk-high density polyethylene composite - 199539 Naurah Mat Isa (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2006